Development of Hygiene and Sanitation Learning Module Based on Problem Based Learning (PBL) Model " - Nova Nelsya Ariani; Linda Rosalina; Rahmiati Rahmiati; Ambiyar Ambiyar (EDUTEC : Journal of Education And Technology, 2022)
The learning process requires additional references in addition to package books and LKS. Based on the results of observations and interviews, it was found that there were no special modules in hygiene and sanitation learning. But there is some kind of teaching material or it can be said to be a small shaped module (mini module). The existing teaching materials have various kinds of obstacles so that students become complicated, difficult to read and do not cause interest to readers and it is difficult to understand the content of the problem because it is not equipped with sample images that show the forms of equipment used. This study aims to develop learning media in the form of Hygiene and Sanitation modules based on Problem Based Learning (PBL) models that meet the validity aspects of the media. The research method used is the development (R&D) of the 4-D model, including the Define, Design, Develop and Disseminate stages, but the Disseminate stage is not carried out. The results showed validity in the validation of learning media with didactic aspects of 95%, construction aspects of 96% and techniques of 95% with an average of 95.66% of very valid categories. In the validation of the material in the module, results were obtained on the material aspect of 95%, the language aspect of 96% and the presentation aspect of 98% with an average of 96.33% of the category is very valid. Based on the results obtained, it shows that the learning media for the Hygiene and Sanitation module based on Problem Based Learning (PBL) models is suitable for students in learning.